City and modernity: Processes of modernization in Belém of Pará between 1930-1960 - Pont Vidal, Celma Chaves (Universidad Nacional de Mar del Plata. Facultad de Arquitectura, Urbanismo y Diseño, 2018)
This paper presents a review in the modernizing process developed in Belém City, capital of the Pará State, in the Brazilian Amazon, from 1930 to 1960. It highlights aspects of this modernization noticed in transport infrastructures, in road system, and in water and sewage networks. Aiming to reflect on the resources/means in which the urban ideas and practices defended by the local social strata – state, contractors, and civil society – shaped the Capital City, this paper uses sources such as reports from the municipal and state governments, the companies, and other agents related to changes in the Capital City, as well as mapping to represent these noticed changes. With the aid of the documented-based source, it has been found that the financial and ideological interests of the agents responsible for the Belém City landscape design was decisive for accomplishing this modernizing process, prioritizing the most valued areas of the city where society groups with greater purchasing power were concentrated.